Ready to Move: A Unique University Worksite Wellness Initiative - Mariah Deinhart; Carol Kennedy-Armbruster (The Ohio State University Libraries, 2019)
Background: Ready to Move (RTM), a university worksite wellness program, was implemented to get employees moving more and sitting less by combining student health coaching and activity trackers (AT's). Aim: This article provides program specifics and survey data outcomes to facilitate ideas for university faculty, staff and student collaboration. The intent of the article is to provide an example of how academic classes can contribute to employee worksite wellness programming within a university. Methods: Twelve cohorts (2015 - 2017) comprised of 295 university employees received Fitbit Flex ATs and health coaching from students enrolled in a physical activity (PA) behavioral interventions class during a 10-week program. The employees met with their student coach eight times to learn how to use their AT and set movement goals. Employee's completed self-reported surveys on average PA days and PA confidence pre/post program. Results: Findings revealed RTM significantly impacted employees average number of PA days and their confidence in ability to sustain PA. Employee qualitative comments revealed RTM instilled the importance of utilizing ATs combined with student engagement made the experience enjoyable and effective. Conclusion: RTM's combination improved employee movement outcomes and provided additional programming ideas for the employee wellness program at a large Midwestern university.